SALTWATER FISH CONSUMPTION AND THE RISK OF STROKE IN COASTAL POPULATION - Haq, Abiyyu Didar; Harahap, Herpan Syafii; Wahyudi, Safat; Susilawati, Ni Nyoman Ayu (MNJ (Malang Neurology Journal), 2024)
Indonesia, consisting of tens of thousands of islands, has a rather long coastline with relatively high percentage of it is population that lives in the coastal area. High consumption of saltwater fish in the coastal population is an inevitability. Several studies have observed a relation between saltwater fish consumption and the risk of stroke with contradicting results, protective effect on one side and harmful on the other. The protective effect is mainly mediated by the poly-unsaturated fatty acid (PUFA) content of the saltwater fish while the harmful effect is mediated by the sodium content. PUFA exerts its protective effect through it is antioxidant effect on the endothelial wall, anti-inflammatory effect and the activation of anti-apoptotic pathways in the state of ischemic stroke while sodium increases the risk of hypertension which is the main predisposing factor for stroke and induces anatomical remodeling of the endothelial wall as well as functional abnormalities. Several public health interventions have been carried out to mitigate the harmful effect of the sodium content of saltwater fish yet there hasn’t been a specific intervention for coastal population.